Analysis of effectiveness of online learning pandemic COVID-19 in prosthetic orthotic major - Nur Rachmat (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Background: Prosthetic Orthotics Major in Polkesta conducts online lectures in order to support government efforts in the even semester 2019/2020, starting from March 2020 until the end of the even semester. Several online applications are used in support of online lectures. Method: This study was conducted to analyze the effectiveness of online learning during the covid19 pandemic in the orthotic prosthetic Major in Polkesta Indonesia. This is a quantitative descriptive study. This research uses a survey method using an online Google Form questionnaire. The population is students of Prosthetic Orthotic Major, There are 322 respondents who are willing to contribute to the research. Results: there are 67 % of students felt less effective, 14% of students felt ineffective, and 20 % of students felt effective. Applications used by students and felt to be effective are Google meet, google classroom and WhatsApp Group. Learning methods using Life video conferencing are felt to be the most effective Conclusion: online learning process in the prosthetic orthotic major is not felt to be quite effective by students.